2014
DOI: 10.2106/jbjs.m.00919
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infections in Orthopaedic Surgery Demonstrate Clones Similar to Those in Orthopaedic Staphylococcus aureus Nasal Carriers

Abstract: Surgical site infections might be more frequently caused by endogenous transmission than was previously assumed. Perioperative preventive efforts must focus more on this route to further decrease the risk of postoperative orthopaedic infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 39 publications
2
34
1
Order By: Relevance
“…It was shown as early as the 1950s that S. aureus nasal carriers have an increased risk of developing postoperative wound infections, as compared to noncarriers (Weinstein 1959;Williams et al 1959). This has more recently been verified in patients undergoing orthopedic (Skramm et al 2014) and cardiac surgery (Kluytmans et al 1995). Also S. aureus nasal carriers have a greater risk of developing bacteremia (Wertheim et al 2004a).…”
Section: Infectionmentioning
confidence: 97%
See 1 more Smart Citation
“…It was shown as early as the 1950s that S. aureus nasal carriers have an increased risk of developing postoperative wound infections, as compared to noncarriers (Weinstein 1959;Williams et al 1959). This has more recently been verified in patients undergoing orthopedic (Skramm et al 2014) and cardiac surgery (Kluytmans et al 1995). Also S. aureus nasal carriers have a greater risk of developing bacteremia (Wertheim et al 2004a).…”
Section: Infectionmentioning
confidence: 97%
“…It has been shown that persistent nasal carriers have an increased risk of infection as compared to non-carriers (Kluytmans et al 1995;Wertheim et al 2004a;Skramm et al 2014) and that >80 % of the infections are caused by the carrier strain, as a result of endogenous transmission (von Eiff et al 2001;Wertheim et al 2004a). Eradication of nasal carriage has proven effective in the reduction of endogenous infections (Talon et al 1995;Kluytmans et al 1996a;Kluytmans et al 1996b).…”
Section: Transmission Routes and Sources (Papers III And Iv)mentioning
confidence: 99%
“…The ecologic niche of S aureus is the nasal passages [30], and the association between nasal carriage of S aureus and surgical site infection (SSI) was established in 1959 [33]. Carriers of S aureus are two to nine times more likely to develop an SSI, and it has been shown that 85% of SSIs can be traced to endogenous colonization of the patients [6,18,25,31,34]. In 1999, the Centers for Disease Control and Prevention (CDC) recognized nasal colonization of S aureus as a risk factor for SSI [20].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying carriers early is vital for patients undergoing surgery, as MRSA is a leading cause of surgical-site infection (SSI) (22, 24). Patients undergoing cardiothoracic and neurological surgery are at an elevated risk of developing SSIs due to endogenous and hematogenous pathogen access to the thoracic and cranial cavities, with SSIs from MRSA strongly correlating with postoperative morbidity and mortality (22, 2426). In spite of these risks, cardiothoracic and neurological surgery patients appear to be at a low risk for contracting MRSA.…”
Section: Introductionmentioning
confidence: 99%